Brand Image as a Mediator of Service Quality, Price, and Purchase Intention: Evidence from Tokopedia - Maria Natalia; Kamaruzzaman Onaning (ESENSI: Jurnal Manajemen Bisnis, 2025)
This study investigates the influence of service quality and price on brand image, and the subsequent impact on consumers’ purchase intention within the Tokopedia e-commerce platform in the DKI Jakarta region. A quantitative approach with a causal research design was employed, with data collected through a structured Likert-scale questionnaire administered to 187 respondents selected via incidental sampling. Data were analysed using Structural Equation Modelling (SEM) with LISREL 8.8 software. The findings confirm that all five hypotheses are supported at the 5% significance level. Service quality emerged as the strongest predictor of brand image (β = 0.66; t = 10.29), while brand image proved to be the strongest predictor of purchase intention (β = 0.47; t = 5.39). Mediation analysis reveals that brand image functions as a partial mediator: the indirect effect of service quality on purchase intention through brand image (0.310) substantially exceeds its direct effect (0.190), while the indirect effect of price (0.122) complements its direct effect (0.250). The coefficients of determination of 74% and 70% for the respective structural equations indicate strong model fit. These findings imply that a synergistic marketing strategy integrating service quality enhancement, competitive pricing, and brand image strengthening constitutes the most effective approach to stimulating purchase intention on digital marketplace platforms in Indonesia.